2008
DOI: 10.1161/hypertensionaha.107.093682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antecedent Hypertension and Follow-Up Blood Pressure on Outcomes After High-Risk Myocardial Infarction

Abstract: Abstract-The influence of blood pressure on outcomes after high-risk myocardial infarction is not well characterized. We studied the relationship between blood pressure and the risk of cardiovascular events in 14 703 patients with heart failure, left ventricular systolic dysfunction, or both after acute myocardial infarction in the Valsartan in Myocardial Infarction Trial. We assessed the relationship between antecedent hypertension and outcomes and the association between elevated (systolic: Ͼ140 mm Hg) or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 38 publications
5
51
1
4
Order By: Relevance
“…These results fit well with recent prospective STEMI registry studies which reported a prevalence between 60 and 70 % [23,24]. Antecedent HTN has been acknowledged as significant risk factor for adverse outcome in survivors of acute MI for many years [4][5][6]. For instance, Thune et al found that antecedent HTN at the time of MI was strongly associated with an increased risk of future heart failure, stroke, cardiovascular death and a composite endpoint consisting of death, myocardial infarction, heart failure, stroke, or cardiac arrest in more than 14.000 patients included in the VALI-ANT trial (Valsartan in Myocardial Infarction Trial) [4].…”
Section: Antecedent Hypertension Baseline Risk Profile and Clinical supporting
confidence: 91%
See 3 more Smart Citations
“…These results fit well with recent prospective STEMI registry studies which reported a prevalence between 60 and 70 % [23,24]. Antecedent HTN has been acknowledged as significant risk factor for adverse outcome in survivors of acute MI for many years [4][5][6]. For instance, Thune et al found that antecedent HTN at the time of MI was strongly associated with an increased risk of future heart failure, stroke, cardiovascular death and a composite endpoint consisting of death, myocardial infarction, heart failure, stroke, or cardiac arrest in more than 14.000 patients included in the VALI-ANT trial (Valsartan in Myocardial Infarction Trial) [4].…”
Section: Antecedent Hypertension Baseline Risk Profile and Clinical supporting
confidence: 91%
“…The median time between the index event and CMR scan was 3 [2][3][4] days. CMR findings and their relation with antecedent HTN are shown in Table 4.…”
Section: Antecedent Hypertension and Cardiovascular Magnetic Resonancmentioning
confidence: 99%
See 2 more Smart Citations
“…Se habla de causalidad reversa cuando la enfermedad (como infarto de miocardio) reduce el factor de riesgo primario (en este caso, la presión diastólica o sistóli-ca). Lo cual muestra una relación entre disfunción cardiaca y curva J sistólica o diastólica, como se puede observar en el estudio VALUE (8) , en donde luego de un infarto de miocardio, aquellos pacientes con una PS sostenida <100 mmHg en los siguientes meses de control (mes 1, 3 y 6) tuvieron peores eventos cardiovasculares, lo cual a su vez fue más frecuente en aquellos con mayor incidencia de ondas Q. Es por esta razón que, diversos estudios que han evaluado el impacto de la presencia de la curva J no consideran aquellos que han incluido a pacientes con infarto de miocardio. Otras enfermedades que se vinculan con una disminución de la presión sanguínea incluyen a neoplasias y malnutrición.…”
Section: Curva J Y Causalidad Reversaunclassified